Near-Modul Kuat Faktor - Meryta Febrilian Fatimah; Darmawati Darmawati (Jambura Journal of Mathematics, 2023)
Near-ring is a generalization of ring. In ring theory, let R be a ring over addition and multiplication operation with unity element and G be a commutative group under addition operation. Then G together with scalar multiplication of R and holds several axioms called module over ring. Let N be a near-ring, here we can construct the module over near-ring called near-module. We have three definitions of module over near-ring, such that, near-module, modified near-module, and strong near-module. Then we showed that strong near-module can be constructed into strong near-module factor as well as module factor in G. Furthermore, we generalized the fundamental theorem of homomorphism in module over ring to strong near-module over strong near-ring.